Characterization of a Josephson array for pulse-driven voltage standard in a cryocooler. (January 2017) - Sosso, A.; Durandetto, P.; Trinchera, B.; Kieler, O.; Behr, R.; Kohlmann, J.
Highlights: A cryocooled pulsed Josephson standard is presented. Cryocoolers allow simpler operation and can reduce cables, increasing signal accuracy. Results are discussed analyzing the spectra of signals and comparing with observations in liquid helium. Abstract: Pulse-driven Josephson junctions allow the synthesis of very precise both spectrally pure and arbitrary wave forms with frequencies up to the megahertz range. We investigated the properties relevant for metrological applications of series arrays with 4000 Josephson junctions fabricated at PTB in cryocooler and liquid helium. DC electrical parameters were evaluated and Shapiro steps dependence on operating conditions was studied. Both cooling techniques provided similar results for all relevant parameters. In particular, we were able to observe Shapiro step widths of more than 1 mA in cryocooler. Yet, we found that some specific effects related to the different thermal conditions must be taken into account for proper operation in cryocooler.